Fast exchange of strontium between hair and ambient water: Implication for isotopic analysis in provenance and forensic studies - Hu, Lihai; Fernandez, Diego P.; Cerling, Thure E.; Tipple, Brett J. (PLOS ONE, 2020)
Trace elements in hair originate from intake (e.g., diet, inhalation, skin absorption), are transported in the bloodstream, and then incorporated during hair formation. However, the trace element abundance and isotopic compositions may be altered by post-eruption environmental processes. Such alterations must be addressed to obtain a meaningful interpretation of hair analysis for biomonitoring. In this study, we used strontium (Sr) isotopic analysis together with sorption kinetics of ionic Sr to quantify the rate and extent of replacement of endogenous Sr in hair by exogenous Sr from ambient water. We found that with only 10 minutes of exposure at room temperature (22°C), more than 30% of original endogenous Sr in hair was replaced with exogenous Sr from the solution. After 16 days of exposure to the solution, more than 90% of endogenous Sr was replaced, with a warmer temperature (60°C) accelerating the exchange substantially. We also found that acid leaching of exposed hair did not remove or isolate the exogenous Sr; therefore, neither the original endogenous nor the exogenous 87Sr/86Sr signal could be separated. Nonetheless, these findings illustrated that the quantitative correlation between the fraction of exogenous Sr and the soaking time, if established, could be used to estimate the length of water contact time for hair in forensic studies. Even if such time since initial contact cannot be established, the combination of acid leaching and 87Sr/86Sr analysis of hair samples may still be valuable in provenance studies to identify recent changes in the exogenous Sr pool, including movements or changes in water source.